BERTAHAN DI TENGAH PERGULATAN ZAMAN (Kajian Sejarah Sosial-Ekonomi Komunitas Keturunan Hadrami di Yogyakarta Abad Ke-20) - Fatiyah . (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
The community development of the Hadrami (jamaah) in Yogyakarta in the 20th was not separated from the life construction of the former Hadrami generation. All social process and experiences have influenced their point of view and dynamism going on the community social life in Yogyakarta. In social context, the Hadrami generation of Yogyakarta who were born in the early 20th century has been the